2021
DOI: 10.3389/fpubh.2021.556648
|View full text |Cite
|
Sign up to set email alerts
|

Sickness Absence and Disability Pension in the Very Long Term: A Finnish Register-Based Study With 20 Years Follow-Up

Abstract: Sickness allowance is paid for short-term sickness absence and is thus an indicator of temporary ill health, but it is also associated with a heightened risk of receiving disability pension. Using event history analysis, we examined the long-term risk for disability pension receipt after first observed receipt of medically certified sickness allowance in each single year after sickness allowance was first recorded. Utilizing longitudinal data from the Finnish population register, covering the period 1989–2010,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…One outcome that is clear and stands out is that higher the number of spells and number of days and more importantly the higher the number of spells of days more than four weeks (long-term spells), the possibility of disability retirement goes up by at least three times both in the penultimate and the final calendar year. While this aligns with previous studies [ 22 , 23 , 56 ] that report the impact of long-term absence, this study provides new insight to understand the absence behavior over two years. The implication of this is if a police officer request for long-term sickness leaves in higher frequency in a year, with one or more term of four weeks in year, immediate intervention is recommended to mitigate possibility of filing for disability retirement.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One outcome that is clear and stands out is that higher the number of spells and number of days and more importantly the higher the number of spells of days more than four weeks (long-term spells), the possibility of disability retirement goes up by at least three times both in the penultimate and the final calendar year. While this aligns with previous studies [ 22 , 23 , 56 ] that report the impact of long-term absence, this study provides new insight to understand the absence behavior over two years. The implication of this is if a police officer request for long-term sickness leaves in higher frequency in a year, with one or more term of four weeks in year, immediate intervention is recommended to mitigate possibility of filing for disability retirement.…”
Section: Discussionsupporting
confidence: 90%
“…The study also aims to determine which measure of sickness absence is the strongest marker for disability retirement. The outcome of this study will help identify the key reasons predictors of disability retirement among police personnel in the UAE and propose strategies to balance prevention of income loss and mitigate the substantial costs to society and the government due to loss of workforce [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sex differences in disease susceptibility and incidence for diseases such as common mental disorders with a higher incidence among women than men, may also have contributed to the observed differences. A Finnish register-based study with a 20-year follow-up found no sex difference in the long-term risk of DP following the first SA spell [ 41 ]. However, the outcome of interest was DP, while we measured both SA and DP with different lengths and sequences over the working life course, and therefore, we were also able to capture individuals with longer, but still temporary SA, with the possibility of later returning to the labour market.…”
Section: Discussionmentioning
confidence: 99%
“…Within the time span of a few years, the number of SA days received increases the risk of becoming a disability pensioner (Gjesdal and Bratberg 2003). However, over the course of 20 years, any amount of SA received is associated with a heightened risk for DP (Klein et al 2021). Therefore, the first observed SA receipt is an important indicator for future DP receipt, as the latter is almost always a permanent exit from the labor market (Laaksonen and Gould 2015;Saarela and Finnäs 2002).…”
Section: Conceptual Frameworkmentioning
confidence: 99%